Analysis of the Effects of Laser Cutting Process Parameters on the Kerf Width of Plywood Using the Taguchi Method - ikhsan Muhammad Ikhsan; Alang Sunding (METAL: Jurnal Sistem Mekanik dan Termal, 2026)
Laser cutting is widely used in the manufacturing industry due to its ability to produce high-precision cuts. However, the quality of the cutting results is strongly influenced by the process parameters applied. This study aims to analyze the effects of laser cutting process parameters on the kerf width of plywood material and to determine the optimal parameter conditions using the Taguchi method and analysis of variance (ANOVA). The investigated parameters include material thickness (1, 2, and 3 mm), cutting speed (30, 40, and 50 mm/s), and laser current (20, 30, and 40 A). The experimental design was developed using a Taguchi orthogonal array, while the quality characteristic employed was the smaller-is-better criterion. The analysis results indicate that material thickness is the most influential factor affecting kerf width, with a contribution of 94.99%. Cutting speed and laser current exhibit smaller effects and are not statistically significant. The optimal conditions for minimizing kerf width are obtained at a material thickness of 3 mm, a cutting speed of 50 mm/s, and a laser current of 20 A. The ANOVA results confirm the consistency of the Taguchi analysis, leading to the conclusion that controlling process parameters—particularly material thickness—plays a crucial role in improving the precision and quality of laser cutting results on plywood materials.